Carry Over Mechanism As An Efficient Legislative Instrument For Strategic Bills - Guasman Tatawu; Fareed Mohd Hassan; Wahyu Aliansa; Muhammad Awaluddin Rasake (APHTN-HAN, 2026)
This study explores the carryover mechanism in the legislative process of the Indonesian House of Representatives. It discusses the carryover mechanism in the legislative process in the Indonesian House of Representatives as an instrument of efficiency that allows a bill to be discussed across different periods without starting over from the beginning. This mechanism is assessed as capable of overcoming legislative stagnation, which is a consequence of changing members of the DPR, as seen in the successful passage of the Criminal Code Bill and the TPKS Bill, both approved after experiencing the carryover mechanism. Carryover is present as an innovation in law aimed at solving classic legislative problems, such as many priority bills failing to be approved within one period due to limitations of time, political dynamics, and the complexity of discussions. From the perspective of efficiency, carryover can prevent waste of resources and strengthen the principle of value for money in public administration, while also ensuring legislative continuity across periods, as evidenced by the ratification of the Criminal Code Bill and the TPKS Bill. However, from the legitimacy perspective, this mechanism raises constitutional concerns because it can cause a legitimacy deficit when new members of the DPR continue discussions without proper validation, repetition, or public participation. An analysis using constitutional law shows that carryover can be viewed as legitimate if it is balanced with procedures that guarantee principles of political representation, transparency, and accountability. Meanwhile, a review through progressive legal theory confirms that law must adapt to societal needs and substantive justice, so carryover can only be effective if managed transparently, participatorily, and responsibly.